The Role of Hope and Psychological Need Support in the Prediction of Academic Achievement and Psychological Well-Being of NCAA Division I Student-Athletes - Scislo, Brian (My University, 2018)
Hope is a psychological strength that promotes adaptive psychological and performance outcomes. In addition, an environment which supports an individual’s psychological need to feel autonomous, competent, and connected has been shown to elicit more autonomous functioning, enhanced motivation, increased well-being, and greater academic performance. The purpose of this study was to test the effects of autonomous self-regulation and hope on the relationship between psychological need support, academic achievement, and psychological well-being. Using structural equation modeling (SEM), the plausibility of a proposed model is tested in a sample of 303 collegiate student-athletes. The Learning Climate Questionnaire, Perceived Competence for Learning Scale, Sense of Relatedness Scale, Learning Self-Regulation Questionnaire, Adult Hope Scale, Academic-Specific Hope Scale, and Satisfaction With Life Scale were used. Semester grade point average and demographic information were also gathered. The results of the study demonstrate that increased environmental supports for autonomy, competence, and relatedness predict increased autonomous self-regulation, thus positively influencing levels of hope, leading to greater academic achievement and enhanced psychological well-being. Research findings are discussed in reference to the related literature and implications for future research and practice are suggested.
Keywords: positive psychology; education; intercollegiate athletics